2018
DOI: 10.1158/1078-0432.ccr-17-2777
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab plus Lenalidomide after Allogeneic and Autologous Stem Cell Transplantation for Patients with Lymphoid Malignancies

Abstract: Prevention or treatment of relapsed lymphoid malignancies after hematopoietic stem cell transplantation (HSCT) requires novel strategies. We hypothesized that antitumor-cell responses could be enhanced by the addition of lenalidomide to the cytotoxic T-lymphocyte-associated protein 4 inhibitor ipilimumab. We conducted a phase II investigator-initiated trial to assess the safety and activity of ipilimumab and lenalidomide in patients with lymphoid malignancies that relapsed after allogeneic HSCT and in high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Another cohort of 15 patients received ipilimumab at the dose of 5 mg/kg (2, 13). Ipilimumab was given to 10 patients at 3 mg/kg for a total of 2 doses, alternating with lenalidomide (9). In another study, 3 patients received ipilimumab for five cycles with no information available on the dose (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cohort of 15 patients received ipilimumab at the dose of 5 mg/kg (2, 13). Ipilimumab was given to 10 patients at 3 mg/kg for a total of 2 doses, alternating with lenalidomide (9). In another study, 3 patients received ipilimumab for five cycles with no information available on the dose (12).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators reported 35 deaths of which, 10 cases (28%) were GVHD related. Nine studies reported prior history of GVHD in 49% patients (1, 79, 13, 16, 20, 26, 27). Complications, other than GVHD, include hematologic side effects (22%), most notably neutropenia; followed by respiratory and hepatic complications (16% and 14% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, IPI > 0 immediately preceding stem cell collection and the number of chemotherapy regimens received prior to transplantation were predictive of OS, DFS and relapse. Innovative strategies such as the use of immunotherapy post-transplantation in this setting are currently undertaken at our center (30).…”
Section: Discussionmentioning
confidence: 99%
“… 88 Although it serves as an alternative treatment method, HSCT still has a relapse risk among 40%–80% of recipients. 89 Both auto-HSCT and allo-HSCTare the main alternative cellular therapeutic methods to treat leukemia. Auto-HSCT is the appropriate and applicable therapeutic option for multiple myeloma 1 , 18 and HL.…”
Section: Hematopoietic Stem-cell Transplantation To Treat Leukemiamentioning
confidence: 99%